The Novel Toll-Like Receptor 2 Agonist SUP3 Enhances Antigen Presentation and T Cell Activation by Dendritic Cells - Guo, Xueheng; Wu, Ning; Shang, Yingli; Liu, Xin; Wu, Tao; Zhou, Yifan; Liu, Xin; Huang, Jiaoyan; Liao, Xuebin; Wu, Li (Frontiers in Immunology, 2017)
Dendritic Cells (DCs) are highly specialized antigen presenting cells that play crucial roles in innate and adaptive immunity. Previous studies suggested that Toll-like receptor (TLR) agonists could be used as potential adjuvants, as activation of TLRs can boost DC-induced immune responses. TLR2 agonists have been shown to enhance DC-mediated immune responses. However, classical TLR2 agonists such as Pam3CSK4 are not stable enough in vivo, which limits their clinical applications. In this study, a novel structurally stable TLR2 agonist named SUP3 was designed. Functional analysis showed that SUP3 induced much stronger anti-tumor response than Pam3CSK4 by promoting cytotoxic T lymphocytes activation in vivo. This effect was achieved through the following mechanisms: SUP3 strongly enhanced the ability of antigen cross-presentation by DCs and subsequent T cell activation. SUP3 upregulated the expression of costimulatory molecules on DCs and increased antigen deposition in draining lymph nodes. More interestingly, SUP3 induced less amount of pro-inflammatory cytokine production in vivo compared to other TLR agonists such as LPS. Taken together, SUP3 could serve as a novel promising immune adjuvant in vaccine development and immune modulations.